TANGGAP TIGA VARIETAS LADA PERDU TERHADAP PUPUK ORGANIK - YANG NURYANI; PASRIL WAHID (Jurnal Penelitian Tanaman Industri, 1999)
Response of three bushy black pepper vaieties to organic fetilizerResponse of three bushy black pepper varieties to organic fertilizer was studied in Sukamulya Research Insulation, rom February 1992 to August 1995. The plant materials used wee pepper cuttings deived rom generative branches. The field tial with factorial treatments was designed in a random¬ ized block with three replicates and 9 plants per plot The varieties tested were : a) Lampung Daun Lebar (LDL), b) Merapin, and c) Kuching. The organic fertilizer used wee : (a) Control, (b) 800 g OST (organic soil treatment) per plant per year and (c) 20 kg cattle manure per plant per year. The esults indicated that Kuching it the best in terms of the number and length of pimary branches, canopy area, number ofberries per spike, and spike length. Fertilizer ■tauuuuts as well as its interaction with varieties had no significant efect on yield at the first harvest. Catle manure had significant effect on to spiked and dried berries it die second harvest However, based on toul production of dried teed*, var. LDL and Kuching gave a significantly higher yield compared with Merapin.